Effect of Different Density to Growth and Survival of Gurame Seedling - Elisnawati Harun; Yuniarti Koniyo; Juliana Juliana (The NIKe Journal, 2019)
This study aims to determine the effect of different stocking density on the growth and survival of fish fry carp (Osphronemus gouramy). This study used an experimental method. The design used was completely randomized design (CRD) with three treatments and three replications. The results showed that the absolute growth in length and the highest weight shown on treatment A (3 heads / l) respectively of 1.09 and 0.9 g cm, followed by treatment B (5 animals / l) respectively of 0.9 cm and 0.84 g, and the lowest in treatment C (7 animals / l), respectively for 0.86 cm and 0.8 g. Gurame fish seed viability during the study showed treatment A by 82.86% whereas 72.67% of treatment B and C treatment amounting to 83.33%. The results of this study continue with the LSD (Least Significant Difference) with a confidence level of 99%. Keywords: Gurame seedling; Osphronemus gouramy; survival; density; growth